Konsep Pemikiran dan Penegakan Hukum Khalifah Umar Bin Abdul Azis - Mubarak, Muhammad Hilal; Sultan, Lomba; F, Fatmawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In a country, the function of the government is very important, because if the government does not function well it will have a big impact on the stability of a country. Therefore, government must be held by people who understand the function of government. The government is an organization that has the power to create and implement laws and regulations in certain areas. The government has the power and institutions that take care of state matters and the welfare of the people. Umar bin Abdul Aziz was caliph for no more than 3 years, but he succeeded in reviving the glory of Islam as in the days of his predecessors. After he was sworn in as caliph, there were many changes in government policy. He made policies that were different from the previous government in the fields of politics, economics and religion, he also took a firm stance towards government officials.